What the Future of Smart Working Holds for Italian Society - Martini, Elvira; Mebane, Minou Ella; Greco, Luca; Furlan, Claudia (Italian Sociological Review, 2026)
Current literature focuses mostly on the advantages and disadvantaged of smart working (SW); more research is needed to understand if people perceive that in the future, SW will bring beneficial outcomes not only for companies or workers but also for society and improve quality of life. To help fill this research gap, the current study investigated how people perceived SW will impact aspects of society such as neighborhoods, environment, and communities, work-life balance and economy (through the increase in female employment). Two hundred fifty-six smart workers participated in this research. Our principal findings reveal that SW could promote a better quality of life: participants mostly believe that in the future SW will contribute to diminishing CO2 emissions, reducing traffic, decongesting crowded areas, and to revitalizing social life in dormitory neighborhoods. Participants had less confidence that SW would help close the work gender gap, reducing barriers to women’s entry into the workforce and increasing work opportunities for housewives. Women, moreover, were less convinced than men that through SW they would obtain a better work-life balance.